Culling the Masses: The Democratic Origins of Racist Immigration Policy in the Americas - David scott Fitzgerald, David Cook-MartÃn (Harvard University Press, 2014)
Juan Bautista Alberdi, the leading Argentine intellectual of the nineteenth century, famously observed that â€œin the Americas, to govern is to populate.â€1 Open immigration policies in the nineteenth century allowed nearly anyone to walk off the docks in Buenos Aires, Havana, New York, or Halifax. By the 1930s, intellectuals from Argentina to Cuba had attached a qualifier to his dictum: â€œto govern is to populate well.â€2 The governments of every independent country in the Americas created the legal and bureaucratic machinery to cull only â€œethnically desirableâ€ human stock from the millions yearning to breathe free. The United States led the way in creating racist policies beginning with its nationality laws in 1790 and its immigration laws in 1803.3 In his book American Ideals written in 1897, just four years before he became president, Theodore Roosevelt praised the democratic wisdom of the United States and the other Anglophone settler societies for selecting immigrants on racial grounds. Like most contemporary leaders, Roosevelt believed that Chinese deserved exclusion because they were racially inferior and incapable of governing themselves in a democracy. He warned against the dangers of business interests attempting to attract Chinese immigrants to work as indentured servants. In Rooseveltâ€™s view, Chinese were only one step up from the descendants of black slaves, which plantation owners had imported to the detriment of free white workers. Democracies needed racist policies to protect their citizens and democracy itself.4 Roosevelt would have been astonished to learn that a century later, a nearly universal consensus took it for granted that democracy and racism cannot coexist. Racial selection of immigrants had become taboo. An academic study of major liberal- democratic countries of immigration in 1995 declared that the â€œboundaries of legitimate discussion of immigration policy are narrow, precluding argument over the ethnic composition of migrant streams, and subjecting those who criticize liberal policies to charges of racism.â€5 The ubiquitous racist immigration and nationality laws that Roosevelt cherished had all but disappeared, beginning with Chile, Uruguay, Paraguay, and Cuba in the late 1930s and early 1940s and finally extending to the United States and Canada in the 1960s and Australia in the 1970s. While immigration policies continue to have a differential impact on particular national- origin groups, and discriminatory practices persist, the history of the region plainly shows that policies have dramatically moved in the direction of non- racial selection.